Enhancing magnetic hardness by sonication assisted synthesis of heterometallic carbonato spin-glass Na[Ni(H2O)4Ru2(CO3)4]·3H2O. Issue 9 (7th January 2020) - Li, Jing-Yu; Tian, Yu-Chen; Feng, Li-Na; Zhou, Zi-Qin; Wang, Lin-Lin; Yang, Jian-Hui; Liu, Bin
Abstract : Sonication assisted synthesis of Na[Ni(H2 O)4 Ru2 (CO3 )4 ]·3H2 O promotes its magnetic hardness affected by crystal defect generation. Abstract : Control of magnetic performances of molecular magnets is essential but few efforts have been documented. A green and efficient sonication assisted synthesis of a new heterometallic diruthenium(ii, iii ) carbonate, Na[Ni(H2 O)4 Ru2 (CO3 )4 ]·3H2 O (1 ), was carried out by self-assembling in aqueous solution. Compound 1 exhibits spin-glass behavior below ∼5.0 K, and a systematic investigation of the ultrasonic irradiation influence on the powder samples reveals that their coercivity increases from 50 Oe to 743 Oe with the control of ultrasonic power under appropriate conditions.